Surveillance and privacy in the digital age : European, transatlantic and global perspectives - Vavoula, Niovi; Mitsilegas, Valsamis (London [England] : Hart Publishing, 2021)
"What impact has the evolution and proliferation of surveillance in the digital age had on fundamental rights? This important collection offers a critical assessment from a European, transatlantic and global perspective. It tracks four key dimensions: digitalisation, privatisation, de-politicisation/de-legalisation and globalisation. It sets out the legal and policy demands that recourse to 'the digital' has imposed. Exploring the question across key sectors, it looks at privatisation through the prism of those demands on the private sector to co-operate with the state's security needs. It goes on to assess de-politicisation and de-legalisation, reflecting the fact that surveillance is often conducted in secret. Finally, it looks at applicable law in a globalised digital world. The book, with its exploration of cutting-edge issues, makes a significant contribution to our understanding of privacy in this new digital landscape."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Privacy, Right of; Computer security -- Law and legislation; Computers -- Law and legislation; Data protection -- Law and legislation; Privacy law; Electronic books